Hidden Dynamics of Religion and Human Rights in Central and Eastern Europe - Máté-Tóth, András (Religions, 2023)
The relationship between human rights and religion cannot be seen as a relationship between two entirely distinct sets of values Human rights are deeply rooted in the Judeo-Christian religious tradition. However, throughout history religious institutions have interpreted human rights differently and have supported or hindered their implementation. This paper discusses the relationship between human rights and religion in the social and cultural matrix of post-communist Central and Eastern Europe. Our statistical analysis focuses on Hungary as an example of the region. In our view, the variations in the relationship between human rights and religion in Central and Eastern Europe are primarily determined by the region’s wounded collective identity and the resulting overriding national and state security needs. Politically and culturally, the region is characterized by its betweenness, embodied in centuries of vulnerability to the great powers. Therefore, the social status and political discourse of human rights and religion should be tied to this primary regional marker. While examining the relationship between religion and human rights, we should be aware that the primary relationship is between human rights and the collective identity of the nation-state and between religion and the identity of the nation-state.